A Review of Motivational Influences of Emotions on Academic Goal Pursu - Deepmala, (JOURNAL OF INDIAN EDUCATION, 2021)
Academic performance has long been assumed as the baseline to measure the progress of the child both in schools as well as in life. It can be both, a source of stress and a source of relief and motivation for further actions. Yet, the educators are still inquisitive to explore the factors responsible to promote the academic achievement. This paper looks upon educational goals as the central objective of study and emphasises the role of emotions as the motivational factors to propel the academic goal pursuit of the students in the right direction. It tries to revisit the question why certain students are so motivated to pursue their goals despite challenges and difficulties whereas others find excuses and shut themselves from further growth.